Using of innovative methods in physical training of students of higher educational institutions of Ukraine Ministry of Internal Affairs - Yu.A. Kompaniets (H.S. Skovoroda Kharkov National Pedagogical University, 2013)
It is analyzed the innovations in organization of special physical training of future law enforcement officers. It is shown those interactive methods of teaching which can be reasonably used in the process of physical training of students of higher educational institutions of Ukraine's Ministry of Internal Affairs. It is proved that their usage is possible only after study of basic technology - the whole set of methods and actions which are defined by the normative documents of Ministry of Internal Affairs. It is shown the significance of material and technical provision and also the stages of preparation to carrying out the work in small groups, role plays, trainings. It is shown the peculiarities of usage of different interactive methods in educational process of students. It is given the scheme of conducting of role play and it is shown the main moments which should be taken into account. The usage of interactive methods in teaching assists the future law enforcement officers not only to imagine themselves in definite situation but also to receive the real psychophysiological feelings and understand the consequences from making different decisions, to get definite practical experience without real threat to their lives.